Anode materials and batteries
By forming a cladding layer of amorphous carbon and fast ion conductors on the surface of the graphite core, the problem of the decrease in energy density and poor circulation stability of the lithium battery negative electrode material during fast charging is solved, and high energy density and excellent circulation performance are achieved.
Patent Information
- Application Number
- CN202411951909.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
The energy density of existing lithium battery negative electrode materials decreases during fast charging, which affects the circulation stability. After graphite is combined with carbon binder, the fast charging performance is improved but the circulation performance is reduced.
By forming a cladding layer on the surface of the graphite core, the cladding layer includes amorphous carbon and fast ion conductors, reducing the direct contact between graphite and electrolyte, reducing the barrier to desolvation of lithium ions, improving lithium ion transmission efficiency, and improving volume expansion.
The high energy density of the negative electrode material under fast charging conditions, excellent first-time Coulomb efficiency and long cycle stability are achieved.
Smart Images

Figure CN119764393A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of negative electrode materials, and in particular, to negative electrode materials and batteries. Background Art
[0002] Electric new energy vehicles are the future development direction of the automobile market, and their core components are lithium-ion batteries. With the development of the market, the demand for high-capacity density batteries is getting higher and higher. The use of new high-specific capacity positive and negative electrode materials is one of the important ways to increase the energy density of batteries. With the promulgation and implementation of battery regulations, ESG (Environmental, Social and Governance) has become a universally recognized standard and common language. The society has begun to pay attention to products that meet the ESG concept. The field of negative electrode material technology, as an environmentally friendly material that meets the social concept of ESG, has been receiving increasing attention, and the requirements for negative electrode materials are also increasing.
[0003] Graphite is the mainstream negative electrode material for lithium batteries on the market due to its advantages such as high stability, good conductivity and wide sources. In order to improve the fast charging performance of negative electrode materials and reduce the expansion of negative electrode materials during the cycle, graphite material particles are generally subjected to secondary granulation. However, after the graphite material is compounded with a carbon binder, although the fast charging performance is slightly improved, it will cause the energy density of the negative electrode material to decrease and will also affect the cycle stability of the negative electrode material. Summary of the invention
[0004] The present application proposes a negative electrode material and a battery. By forming a coating layer on the surface of a graphite core, the negative electrode material can meet the fast charging requirements. The negative electrode material also has a high specific capacity, first coulombic efficiency and cycle stability.
[0005] In a first aspect, the present application provides a negative electrode material, the negative electrode material comprising a core and a coating layer, the core comprising graphite, the coating layer comprising amorphous carbon and a fast ion conductor;
[0006] The negative electrode material is tested by Raman scanning to obtain i Raman spectrum curves, i>2000; each Raman spectrum curve has a peak at 1345 cm -1 ~1355cm -1 There is a first characteristic peak in the wavelength range, at 1570cm -1 ~1610cm -1 There is a second characteristic peak within the wavelength range; in the i Raman spectra, the average value of the peak area ratio of the first characteristic peak to the second characteristic peak is A, 2.0≤A≤3.0; the distribution width of the peak area ratio data of the i Raman spectra is P, P<0.5.
[0007] In some embodiments, in the i Raman spectra, the average value of the peak intensity ratio of the first characteristic peak to the second characteristic peak is B, and 0.7≤B≤1.5.
[0008] In some embodiments, (AB) / P>3.
[0009] In some embodiments, the average particle strength of the negative electrode material is Q%, and Q / A is less than 5.0.
[0010] In some embodiments, the average particle strength of the negative electrode material is Q%, 1≤Q≤15.
[0011] In some embodiments, the graphite includes at least one of natural graphite and artificial graphite.
[0012] In some embodiments, the fast ion conductor includes at least one of a titanium ion compound, a niobium ion compound, and a vanadium ion compound.
[0013] In some embodiments, the fast ion conductor is distributed within the amorphous carbon.
[0014] In some embodiments, the coating layer has an average thickness of 5 nm to 20 nm.
[0015] In some embodiments, the volume median particle size D50 of the negative electrode material is 2 μm to 20 μm.
[0016] In some embodiments, the specific surface area of the negative electrode material is 0.5 m 2 / g~5m 2 / g.
[0017] In some embodiments, the tap density of the negative electrode material is 0.5 g / cm 3 ~1.5g / cm 3 .
[0018] In some embodiments, the lithium ion diffusion coefficient of the negative electrode material is greater than or equal to 0.49*10 -7 cm 2 / S.
[0019] In a second aspect, the present application provides a battery, comprising the negative electrode material described in the first aspect.
[0020] The technical solution of this application has at least the following beneficial effects:
[0021] The negative electrode material provided by the present application comprises a core of graphite, a coating layer comprising amorphous carbon and a fast ion conductor, amorphous carbon can reduce the direct contact between graphite and electrolyte, a fast ion conductor can reduce the barrier of lithium ion desolvation, accelerate the efficiency of lithium ion transmission, and the presence of the coating layer can also improve the volume expansion of the negative electrode material, and enhance the first effect and cycle performance of the negative electrode material. In addition, the average value of the peak area ratio of the first characteristic peak to the second characteristic peak of the negative electrode material of the present application is A, and A can characterize the degree of defect and disorder on the surface of the negative electrode material. When A is controlled within the range of 2 to 3, the degree of surface defect of the negative electrode material particles is controlled within a suitable range, and an appropriate amount of surface defects can provide more electrochemical active sites, which is beneficial to improve the capacity of the negative electrode material. However, when the degree of disorder of multiple particles of the negative electrode material is not consistent enough, the lithium ion deintercalation rate between different particles will be inconsistent, affecting the transmission of lithium ions during the charging and discharging process of the prepared battery. Therefore, the present application controls the surface disorder of the negative electrode material, uses the fast ion conductor in the coating layer to increase the ion transmission channels, and controls the distribution width of the peak area ratio data within the range of 0.5, so that the surface disorder of each particle is closer, which can improve the ion transmission efficiency between different negative electrode material particles in the manufactured electrode sheet and improve the fast charging performance of the negative electrode material. The negative electrode material provided by the present application can meet the fast charging requirements, and the negative electrode material also has a high specific capacity, first coulomb efficiency and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application.
[0023] Figure 2 This is a scanning electron microscope image of the negative electrode material prepared in Example 1 of the present application.
[0024] Figure 3 This is a transmission electron microscope image of the negative electrode material prepared in Example 1 of the present application.
[0025] Figure 4a Electron image of the negative electrode material prepared by 1 for this application.
[0026] Figure 4b to Figure 4d The energy dispersive X-ray spectra (EDS) diagrams of different elements of the negative electrode material prepared by implementing 1 of the present application are shown respectively. DETAILED DESCRIPTION
[0027] The following is a preferred implementation of the embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the embodiment of the present invention. These improvements and modifications are also regarded as the protection scope of the embodiment of the present invention.
[0028] In a first aspect, the present application provides a negative electrode material, the negative electrode material comprising a core and a coating layer, the core comprising graphite, the coating layer comprising amorphous carbon and a fast ion conductor;
[0029] The negative electrode material is tested by Raman scanning to obtain i Raman spectrum curves, i>2000; each Raman spectrum curve has a peak at 1345 cm -1 ~1355cm -1 There is a first characteristic peak in the wavelength range, at 1570cm -1 ~1610cm -1 There is a second characteristic peak within the wavelength range; in the i Raman spectra, the average value of the peak area ratio of the first characteristic peak to the second characteristic peak is A, 2.0≤A≤3.0; the distribution width of the peak area ratio data of the i Raman spectra is P, P≤0.5.
[0030] The negative electrode material provided by the present application comprises a core of graphite, a coating layer comprising amorphous carbon and a fast ion conductor, amorphous carbon can reduce the direct contact between graphite and electrolyte, a fast ion conductor can reduce the barrier of lithium ion desolvation, accelerate the efficiency of lithium ion transmission, and the presence of the coating layer can also improve the volume expansion of the negative electrode material, and enhance the first effect and cycle performance of the negative electrode material. In addition, the average value of the peak area ratio of the first characteristic peak to the second characteristic peak of the negative electrode material of the present application is A, and A can characterize the degree of defect and disorder on the surface of the negative electrode material. When A is controlled within the range of 2 to 3, the degree of surface defect of the negative electrode material particles is controlled within a suitable range, and an appropriate amount of surface defects can provide more electrochemical active sites, which is beneficial to improve the capacity of the negative electrode material. However, when the degree of disorder of multiple particles of the negative electrode material is not consistent enough, the lithium ion deintercalation rate between different particles will be inconsistent, affecting the transmission of lithium ions during the charging and discharging process of the prepared battery. Therefore, the present application controls the surface disorder of the negative electrode material, uses the fast ion conductor in the coating layer to increase the ion transmission channels, and controls the distribution width of the peak area ratio data within the range of 0.5, so that the surface disorder of each particle is closer, which can improve the ion transmission efficiency between different negative electrode material particles in the manufactured electrode sheet and improve the fast charging performance of the negative electrode material. The negative electrode material provided by the present application can meet the fast charging requirements, and the negative electrode material also has a high specific capacity, first coulomb efficiency and cycle stability.
[0031] In some embodiments, 2.0≤A≤3.0, specifically, it can be 2.0, 2.1, 2.2, 2.3, 2.5, 2.6, 2.7, 2.8, 3.0 or any value within the range formed by any two of the above values, which is not limited here. In the present application, the A value is controlled within the above range, the structural disorder degree of the coating layer is high, the wettability of the contact interface between the surface of the negative electrode material and the electrolyte can be improved, the interface side reaction of the negative electrode material can be reduced, the consumption of irreversible active lithium ions can be reduced, the lithium ion transmission power can be improved, the interface impedance of the contact interface can be reduced, and the first coulomb efficiency and rate performance of the negative electrode material can be improved.
[0032] In some embodiments, i portions of the peak area ratio data A i The distribution width is P, P≤0.5, P can be 0.5, 0.48, 0.45, 0.3, 0.28, 0.25, 0.2, 0.15, 0.1, 0.05, 0.01 or any value within the range of any two of the above values, which is not limited here. i The distribution width calculation method is to arrange the test results of more than 2000 test points of the surface scan results from small to large, and the distribution width P = (90% point value - 10% point value) / 50% point value. The present application controls the distribution width P within the above range. The smaller the distribution width of the i-part peak area ratio data, the smaller the distribution width of most of the peak area ratio data A i Highly concentrated around the mean, A i The data with values that are too high or too low account for a small proportion, the coating layer on the surface of the inner core is more uniform, and the particles have a high degree of uniformity, which can make the lithium ion deintercalation rate between particles of different negative electrode materials closer, synergistically improve the lithium ion deintercalation rate and transmission efficiency, so that the negative electrode material can meet the fast charging performance.
[0033] In some embodiments, in the i Raman spectra, the average value of the peak intensity ratio of the first characteristic peak to the second characteristic peak is B, 0.7≤B≤1.5. B can specifically be 0.7, 0.75, 0.8, 0.9, 1.0, 1.2, 1.3, 1.4, 1.48, 1.5 or any value within the range formed by any two of the above values, which is not limited here. The present application controls the B value within the above range, and the negative electrode material has a suitable degree of surface defects, which is conducive to improving the capacity and first coulombic efficiency of the negative electrode material.
[0034] In some embodiments, the peak intensity ratio data B of i Raman spectra iThe distribution width is P', P'≤0.5, P can be 0.5, 0.48, 0.45, 0.3, 0.28, 0.25, 0.2, 0.15, 0.1, 0.05, 0.01 or any value within the range of any two of the above values, which is not limited here. i Raman spectrum peak intensity ratio data B i That is, the peak intensity ratio data of different particles of the negative electrode material are highly concentrated, and it can be seen that the particles have a high degree of uniformity. The present application controls the distribution width P' within the above range, so that the lithium ion deintercalation rates between different negative electrode material particles are closer, and the lithium ion deintercalation rate and transmission efficiency are synergistically improved, so that the negative electrode material can meet the fast charging performance.
[0035] In some embodiments, (AB) / P>3, specifically can be 3.01, 3.1, 3.2, 3.5, 4, 5, 6, 7, 10 or any value within the range formed by any two of the above values, which is not limited here. It can be understood that (AB) can characterize the coverage of the coating layer on the surface of the negative electrode material, and P can characterize the uniformity of the distribution state of amorphous carbon and fast ion conductors in the coating layer on the surface of the negative electrode material. When (AB) / P is too small, the P value is too large, that is, the uniformity of the coating on the surface of the negative electrode material decreases. When the negative electrode material is controlled to meet the above relationship in the present application, the surface of the negative electrode material is highly covered by the coating layer. The presence of the coating layer can reduce the occurrence of side reactions between the negative electrode material and the electrolyte, and improve the cycle stability and cycle life of the negative electrode material; and the amorphous carbon and fast ion conductors in the coating layer are more evenly distributed on the particle surface, and the fast ion conductors in the coating layer can also provide a faster channel for lithium ions, thereby improving the fast charging performance of the negative electrode material.
[0036] In some embodiments, the average particle strength of the negative electrode material is Q%, 1≤Q≤15, specifically 1%, 3%, 5%, 7%, 9%, 10%, 12%, 13%, 14%, 15%, or any value within the range formed by any two of the above values, which is not limited here. When the average particle strength of the negative electrode material is controlled within the above range, the structural stability of the negative electrode material is improved, the volume expansion change of graphite can be buffered during the charge and discharge cycle, the particle breakage can be reduced, and the cycle capacity retention rate of the negative electrode material is improved.
[0037] In some embodiments, the average particle strength of the negative electrode material is Q%, Q / A<5.0, and Q / A can specifically be 4.99, 4.85, 4.7, 4.2, 3.5, 3.2, 3.0, 2.5, 2.0, 1.0 or any value within the range formed by any two of the above values, which is not limited here. When the Q / A ratio is too large, it means that the degree of disorder of the surface coating layer of the negative electrode material is too low, and the coating layer is not completely coated on the surface of the inner core, resulting in that the average particle strength will also be slightly affected. During the charge and discharge cycle of the negative electrode material, particles are prone to rupture, side reactions are aggravated, and the capacity retention rate decreases. The present application controls the ratio of the average particle strength of the negative electrode material to the A value within the above range, and the negative electrode material particles can withstand higher pressure (such as rolling pressure), which can increase the compaction density of the negative electrode material. During the electrode coating process, particle breakage can be reduced, and the side reaction between the exposed surface of graphite and the electrolyte can be reduced, thereby improving the rate performance and cycle stability of the negative electrode material.
[0038] In some embodiments, the graphite includes at least one of artificial graphite, natural graphite and microcrystalline graphite. Natural graphite is flake graphite, which is natural phaneritic graphite. It is shaped like fish phosphate, belongs to the hexagonal system, has a layered structure, and has good high temperature resistance, electrical conductivity, thermal conductivity, lubrication, plasticity, acid and alkali resistance and other properties. Artificial graphite is a graphite material obtained by carbonizing organic matter and then subjecting it to high temperature graphitization treatment.
[0039] In some embodiments, the graphite includes at least one of artificial graphite primary particles and artificial graphite secondary particles.
[0040] In some embodiments, the average thickness of the coating layer is 5 nm to 20 nm, specifically 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 18 nm, 20 nm, or any value within the range formed by any two of the above values, which is not limited here. Controlling the coating layer thickness within the above range is beneficial to improving the lithium ion transmission efficiency of the negative electrode material, reducing the occurrence of side reactions between the negative electrode material and the electrolyte, and improving the first coulombic efficiency.
[0041] In some embodiments, the thickness difference between the maximum thickness and the minimum thickness of the coating layer is less than 6 nm, and can be 5.8 nm, 5.5 nm, 4 nm, 3 nm, 2 nm, 1 nm, 0.5 nm, or any value within the range formed by any two of the above values, which is not limited here. If the thickness difference of the coating layer is controlled within the above range, the coating layer on the surface of the negative electrode material particles can be more uniform and of moderate thickness, which can reduce the exposure of the core and improve the tap density and first coulomb efficiency of the negative electrode material.
[0042] In some embodiments, the coating layer includes amorphous carbon and a fast ion conductor, and the coating layer has good compatibility with the electrolyte, thereby ensuring the stability of the electrical performance of the negative electrode material during the charge and discharge process.
[0043] In some embodiments, the amorphous carbon includes at least one of soft carbon, hard carbon and mesophase carbon. The soft carbon is mainly used to perform secondary granulation of the negative electrode material, improve the sphericity of the negative electrode material, reduce the orientation degree, and improve the volume expansion of the negative electrode material.
[0044] In some embodiments, the fast ion conductor includes at least one of a titanium ion compound, a niobium ion compound and a vanadium ion compound. Taking the titanium ion compound as an example, it may be titanium oxide, lithium titanate, and the like.
[0045] In some embodiments, the fast ion conductor is distributed within the amorphous carbon.
[0046] In some embodiments, the specific surface area of the negative electrode material is 0.5 m 2 / g~5m 2 / g; specifically, it can be 0.5m 2 / g, 0.8m 2 / g, 1.0m 2 / g, 1.8m 2 / g, 2.6m 2 / g, 3.5m 2 / g, 4.0m 2 / g, 5.0m 2 / g or any value within the range formed by any two of the above values, which is not limited here. Controlling the specific surface area of the negative electrode material within the above range is beneficial to improving the cycle performance of the battery made of the negative electrode material.
[0047] In some embodiments, the median particle size of the negative electrode material is 2 μm to 20 μm; more specifically, it can be 2 μm, 4 μm, 6 μm, 8 μm, 9 μm, 10 μm, 12 μm, 14 μm, 15 μm, 17 μm, 20 μm, or any value within the range formed by any two of the above values, which is not limited here. The control of the median particle size of the negative electrode material within the above range is conducive to improving the lithium ion deintercalation rate of the negative electrode material, and improving the rate performance and cycle stability of the negative electrode material.
[0048] In some embodiments, the tap density of the negative electrode material is 0.5 g / cm 3 ~1.5g / cm 3 ; Specifically, it can be 0.5g / cm 3 , 0.7g / cm 3 , 0.8g / cm 3 , 0.85g / cm3 , 0.9g / cm 3 , 0.92g / cm 3 , 1.0g / cm 3 , 1.05g / cm 3 , 1.1g / cm 3 , 1.15g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.5g / cm 3 Or any value within the range formed by any two of the above values, which is not limited here. In the present application, the tap density of the negative electrode material is controlled within the above range, which is beneficial to maintain the structural stability of the negative electrode sheet during the cycle process and improve the cycle performance of the negative electrode material and the energy density of the battery.
[0049] In some embodiments, the lithium ion diffusion coefficient of the negative electrode material is greater than or equal to 0.49*10 -7 cm 2 / S, specifically 0.49*10 -7 cm 2 / S, 0.50*10 -7 cm 2 / S, 0.51*10 -7 cm 2 / S, 0.52*10 -7 cm 2 / S, 0.53*10 -7 cm 2 / S, 0.54*10 -7 cm 2 / S, 0.55*10 -7 cm 2 / S, 0.56*10 -7 cm 2 / S or any value within the range formed by any two of the above values, which is not limited here. In some embodiments, the mass percentage of amorphous carbon in the negative electrode material is 0.8% to 1.5%, specifically 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5% or any value within the range formed by any two of the above values, which is not limited here.
[0050] In a second aspect, the present application provides a method for preparing a negative electrode material, the preparation method comprising the following steps:
[0051] Step S10, mixing graphite and a carbon source binder to form a granule to obtain a composite.
[0052] Step S20, adding an appropriate amount of aldehyde reagent to the mixed solution containing the complex, the phenolic reagent and the catalyst to carry out polycondensation reaction, and performing solid-liquid separation on the reaction product to obtain a first precursor.
[0053] Step S30, introducing a gas source containing a coating material and performing chemical vapor deposition on the surface of the first precursor to obtain a second precursor.
[0054] Step S40, carbonizing the second precursor to obtain a negative electrode material, wherein the negative electrode material includes a core and a coating layer, wherein the core includes graphite, and the coating layer includes amorphous carbon and a fast ion conductor.
[0055] The preparation method of the negative electrode material provided by the present application is to first granulate graphite and a carbon source binder to reduce the orientation degree of the secondary graphite particles and reduce the expansion rate; then the granulated product is liquid-phase coated with a phenolic reagent and an aldehyde reagent in a mixed solution, wherein the phenolic reagent and the aldehyde reagent undergo a polycondensation reaction, and the formed chain polymer is uniformly coated on the surface of the secondary graphite particles, which can improve the coating uniformity of the graphite particles, and then a fast ion conductor is formed on the surface of the first precursor by vapor deposition, and finally, after carbonization treatment, a coating layer is formed on the surface of the negative electrode material, and the coating layer includes amorphous carbon and a fast ion conductor. The negative electrode material provided by the present application can meet the fast charging requirements, and the negative electrode material also has a high specific capacity, first coulomb efficiency and cycle stability.
[0056] Step S10, mixing graphite and a carbon source binder to form a granule to obtain a composite.
[0057] In some embodiments, the graphite includes at least one of artificial graphite, natural graphite and microcrystalline graphite. Natural graphite is flake graphite, which is natural phaneritic graphite. It is shaped like fish phosphate, belongs to the hexagonal system, has a layered structure, and has good properties such as high temperature resistance, electrical conductivity, thermal conductivity, lubrication, plasticity, and acid and alkali resistance. Artificial graphite is a graphite material obtained by carbonizing organic matter and then subjecting it to high-temperature graphitization treatment.
[0058] In some embodiments, the graphite includes at least one of artificial graphite primary particles and artificial graphite secondary particles.
[0059] In some embodiments, the specific surface area of the graphite is 0.5 m 2 / g~5m 2 / g; specifically, it can be 0.5m 2 / g, 0.8m 2 / g, 1.0m 2 / g, 1.8m 2 / g, 2.6m 2 / g, 3.5m 2 / g, 4.0m 2 / g, 5.0m2 / g or any value therebetween, which is not limited here. Controlling the specific surface area of the negative electrode material within the above range is beneficial to improving the cycle performance of the battery made of the negative electrode material.
[0060] In some embodiments, the median particle size of the graphite is 2 μm to 20 μm; more specifically, it can be 2 μm, 4 μm, 6 μm, 8 μm, 9 μm, 10 μm, 12 μm, 14 μm, 15 μm, 17 μm, 20 μm or any value therebetween, which is not limited here. The median particle size of the negative electrode material is controlled within the above range, which is conducive to improving the lithium ion deintercalation rate of the negative electrode material and improving the rate performance and cycle stability of the negative electrode material.
[0061] In some embodiments, the tap density of the graphite is 0.5 g / cm 3 ~1.5g / cm 3 ; Specifically, it can be 0.5g / cm 3 , 0.7g / cm 3 , 0.8g / cm 3 , 0.85g / cm 3 , 0.9g / cm 3 、0.92g / cm 3 , 1.0g / cm 3 , 1.05g / cm 3 , 1.1g / cm 3 , 1.15g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.5g / cm 3 Or any value between them, which is not limited here. In the present application, the tap density of the negative electrode material is controlled within the above range, which is beneficial to maintain the structural stability of the negative electrode sheet during the cycle and improve the cycle performance of the negative electrode material and the energy density of the battery.
[0062] In some embodiments, the graphite is tested by Raman scanning, and the graphite has a Raman scanning area of 1345 cm -1 ~1355cm -1 There is a first characteristic peak in the wavelength range, at 1570cm -1 ~1610cm -1 There is a second characteristic peak within the wavelength range, the average value of the peak area ratio of the first characteristic peak to the second characteristic peak is A0, A0<0.5, and the average value of the peak intensity ratio is B0, B0<0.1.
[0063] In some embodiments, the mass ratio of graphite to carbon source binder is (75-93):(25-7), specifically 75:25, 80:20, 85:15, 90:10, 93:7 or any value therebetween, which is not limited here.
[0064] In some embodiments, the granulation method can be any one of heating mixing, heating fusion, and heating kneading.
[0065] Step S20, adding an appropriate amount of aldehyde reagent to the mixed solution containing the complex, the phenolic reagent and the catalyst to carry out polycondensation reaction, and performing solid-liquid separation on the reaction product to obtain a first precursor.
[0066] In some embodiments, the mass ratio of the complex, the phenolic reagent and the catalyst is 50:(1-5):(1-5), specifically 50:1:5, 50:5:1, 50:3:3, etc., which is not limited here.
[0067] In some embodiments, the mixed solution is reacted under stirring, and the stirring method can be any one of mechanical stirring and ultrasonic stirring.
[0068] In some embodiments, the catalyst comprises an acidic catalyst, and the acidic catalyst comprises at least one of hydrochloric acid, sulfuric acid, oxalic acid, and nitric acid.
[0069] In some embodiments, the catalyst comprises an alkaline catalyst, and the alkaline catalyst comprises at least one of sodium hydroxide, potassium hydroxide and ammonia water.
[0070] In some embodiments, the mixed solution further comprises deionized water, and the mass ratio of the deionized water to the complex is 1:1.
[0071] In some embodiments, the phenolic reagent includes at least one of cresol, nonylphenol, aralkylphenol, phenol, and resorcinol.
[0072] In some embodiments, the mass ratio of the complex to the aldehyde reagent is 50:(0.7-10), specifically 50:0.7, 50:1, 50:1.5, 50:3, 50:5, 50:6, 50:7, 50:8, 50:10 or any value therebetween, which is not limited here.
[0073] In some embodiments, the aldehyde reagent includes at least one of formaldehyde, acetaldehyde, and furfural.
[0074] In some embodiments, the polycondensation reaction time is 3 h to 12 h, specifically 3 h, 6 h, 8 h, 9 h, 12 h or any value therebetween, which is not limited herein.
[0075] In some embodiments, the solid-liquid separation comprises at least one of filtration, centrifugation and drying.
[0076] In some embodiments, the drying process comprises at least one of air drying, vacuum drying, freeze drying and spray drying.
[0077] Step S30, introducing a gas source containing a coating material and performing chemical vapor deposition on the surface of the first precursor to obtain a second precursor.
[0078] In some embodiments, the source gas containing the coating material includes a carrier gas, a nanocompound, and water vapor.
[0079] In some embodiments, the nanocompound includes at least one of a niobium-based compound, a vanadium-based compound, and a titanium-based compound.
[0080] In some embodiments, the temperature of vapor deposition is 200°C to 400°C, specifically 200°C, 240°C, 260°C, 300°C, 320°C, 350°C, 380°C, 400°C or any value therebetween, which is not limited here.
[0081] In some embodiments, the time of vapor deposition is 15 min to 60 min, specifically 15 min, 20 min, 30 min, 40 min, 45 min, 50 min, 60 min or any value therebetween, which is not limited here.
[0082] Step S40, carbonizing the second precursor to obtain a negative electrode material, wherein the negative electrode material includes a core and a coating layer, wherein the core includes graphite, and the coating layer includes amorphous carbon and a fast ion conductor.
[0083] In some embodiments, the temperature of the carbonization treatment is 800°C to 1400°C, specifically 800°C, 900°C, 1000°C, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C or any value therebetween, which is not limited here. When the temperature of the carbonization treatment is low, the A value of the coating layer of the negative electrode material is high, that is, the disorder of the coating layer is high, resulting in aggravated interface side reactions and reduced first efficiency of the negative electrode material; when the temperature of the carbonization treatment is too high, the A value of the coating layer of the negative electrode material is low, that is, the disorder of the coating layer is low, resulting in poor interface transport kinetics.
[0084] In some embodiments, the holding time of the carbonization treatment is 3h to 14h, specifically, it can be 3h, 5h, 6h, 8h, 10h, 12h, 14h, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0085] In some embodiments, the carbonization treatment is performed under a protective atmosphere, and the protective atmosphere includes at least one of nitrogen, helium, neon, argon, krypton and xenon.
[0086] In some embodiments, the method further comprises screening and demagnetizing the carbonized product, wherein the mesh number of the screening is 200-400 meshes.
[0087] In a third aspect, the present application provides a battery, comprising the negative electrode material described in the first aspect or the negative electrode material prepared by the method for preparing the negative electrode material described in the second aspect.
[0088] The battery provided in the present application may be a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), including a housing, an electrode assembly, and an electrolyte. The electrode assembly and the electrolyte are both located in the housing. The housing may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), such as when the secondary battery is a soft-pack battery. In other embodiments, the secondary battery may also be a steel-shell battery, an aluminum-shell battery, etc. Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application, such as Figure 1 As shown, the battery includes a housing and an electrode assembly, and the electrode assembly includes a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3, and the separator 3 is arranged between the positive electrode sheet 1 and the negative electrode sheet 2. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet 1, the separator 3 and the negative electrode sheet 2. In other embodiments, the electrode assembly can also be a winding structure, which is formed by stacking the positive electrode sheet, the separator and the negative electrode sheet in sequence and then winding them.
[0089] In some embodiments, the positive electrode sheet 1 includes a positive electrode current collector 101 and a positive electrode active layer 102 disposed on at least one surface of the positive electrode current collector 101 .
[0090] In some embodiments, the positive electrode current collector 101 may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil (aluminum foil or nickel foil, etc.) and a polymer substrate. The positive electrode active layer 102 includes a positive electrode active material, which includes a compound that can reversibly embed and de-embed metal ions.
[0091] In some embodiments, the positive electrode active material may include a lithium transition metal composite oxide, a sodium transition metal composite oxide, etc. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese, and nickel.
[0092] In some embodiments, the positive electrode active material may include but is not limited to lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material (NCM), lithium manganese oxide (LiMn2O4), lithium nickel manganese oxide (LiNi 0.5 Mn1.5 O4) or at least one of lithium iron phosphate (LiFePO4).
[0093] In some embodiments, the negative electrode sheet 2 includes a negative electrode current collector 201 and a negative electrode active material layer 202 disposed on at least one surface of the negative electrode current collector.
[0094] In some embodiments, the negative electrode current collector 201 may use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material layer 202 includes a negative electrode material, which is the negative electrode material of the first aspect described above or the negative electrode material prepared by the above preparation method. The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium ion battery, a sodium ion battery, a solid electrolyte battery, etc., which is not limited here.
[0095] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments. Within the scope of the unchanged main rights, appropriate changes can be made to the implementation. Test method:
[0096] (1) Particle size of negative electrode material and graphite particles:
[0097] The particle size test method refers to GB / T 19077-2016. It can be conveniently measured with a laser particle size analyzer, such as the Mastersizer 3000 laser particle size analyzer produced by Malvern Instruments Ltd., UK. The particle size of 50% of the cumulative volume distribution is D50, i.e. the median particle size.
[0098] (2) Specific surface area test method:
[0099] Under constant temperature and low temperature, after measuring the adsorption amount of gas on the solid surface at different relative pressures, the monolayer adsorption amount of the sample is obtained based on the Brownauer-Etter-Taylor adsorption theory and its formula (BET formula), thereby calculating the specific surface area of the material.
[0100] (3) Test method for tap density: refer to GB / T 5162-2006 / ISO 3953:1993 "Determination of tap density of metal powders" or the equipment manual. Use a tap density meter (Kantako DAT-4-220) for measurement. The number of vibrations is 3000 times.
[0101] (4) Automatic compaction test: The test is performed using an automatic compaction tester. The instrument is first pre-compressed and then reset to zero. 1 g of the sample is weighed and placed in a mold. The mold is installed and placed on an automatic compaction device to test the compaction density of the sample at 5 T.
[0102] (5) SEM test: Scanning electron microscopy characterization was performed on a transmission electron microscope with an operating voltage of 200 kV to observe the structure of the negative electrode material.
[0103] (6) Test method for coating thickness:
[0104] The cross section of the negative electrode material was tested by transmission electron microscopy, and the average thickness of the coating layer was measured in TEM.
[0105] (7) Average particle strength Q of negative electrode materials: The particle strength test was performed using an automatic compaction tester. The sample was placed on a sample table and maintained at a pressure of 5T for 5s. The particle size was then tested and the particle strength was tested using the following formula. Particle strength = 1-(particle size D50 of negative electrode material after pressure maintenance / particle size D50 of negative electrode material before pressure maintenance)*100%. The average particle strength Q was the average of 10 test results.
[0106] (8) Raman test of negative electrode materials:
[0107] Take a small amount of sample (about 1g) and place it on a glass slide to flatten it. After placing the glass slide on the stage, use a 50x objective lens to focus on the sample clearly, scan more than 2000 test points in total, and obtain multiple Raman spectrum curves. Specifically, taking 2601 test points as an example, first select a 100*100μm area, set the step size to 2μm, the laser to 532nm, the laser power to 0.01mW, the exposure time to 5s, the number of cycles to 2 times, and scan a total of 2601 points. Obtain the peak at 1300cm -1 ~1350cm -1 The peak area of the characteristic peak D in the range of 1500 cm -1 ~1580cm -1 The peak area ratio of the G characteristic peak in the range is A i , the peak intensity ratio of the characteristic peak of D to the characteristic peak of G is B i , i = 2601. The average value A of the peak area ratio is at least 200 A i The average value of the peak intensity ratio is at least 200 B i The average value of .
[0108] A i The distribution width is calculated by arranging the test results of more than 2000 test points of the surface scan results from small to large, and the distribution width P = (90% point value - 10% point value) / 50% point value.
[0109] (9) Button cell test: After mixing evenly in a mass ratio of negative electrode material: conductive agent (SuTer P): sodium carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 92:2:2:2, apply it on a copper foil current collector and dry it to obtain a negative electrode sheet for use. The dried electrode sheet is rolled under a pressure of 3MPa to obtain a negative electrode sheet. The battery assembly is carried out in an argon glove box, with a metal lithium sheet as the negative electrode, the electrolyte is 1mol / L lithium hexafluorophosphate + ethylene carbonate (EC) + methyl ethyl carbonate (EMC), and the separator is a polyethylene / propylene composite microporous membrane. The assembled button cell is placed in a constant temperature test box (0℃ / 50℃) and connected to a battery test instrument for testing. The charge and discharge voltage is 0.01~1.5V. The first coulomb efficiency = the first lithium insertion capacity / the first lithium removal capacity.
[0110] (10) Test method for lithium ion diffusion coefficient of negative electrode materials
[0111] The electrode sheet was made according to the negative electrode material: carboxymethyl cellulose (2200): styrene-butadiene rubber (104A): carbon black SP: single-walled carbon nanotube = 95.77: 1.0: 2.0: 1.2: 0.03, and the compaction density was 1.65 g / cm 3 After assembling button half-cells, the lithium ion diffusion coefficient was tested using the PITT method. The test temperature was 25°C and the test voltage range was 0.005-1.5V.
[0112] (11) Full battery test method: The negative electrode materials prepared in the examples and comparative examples were dissolved in deionized water according to a mass ratio of 95.9:1.1:1.3:1.8 for the negative electrode materials, carbon black, carboxymethyl cellulose and styrene-butadiene rubber, respectively, and coated on a copper foil current collector. The negative electrode was vacuum dried to obtain a negative electrode sheet. The surface density of the negative electrode sheet was 80 g / cm 2 The active material lithium iron phosphate positive electrode: the conductive agent Super P: the binder polyvinylidene fluoride (PVDF) was mixed with N-methylpyrrolidone (NMP) in a mass ratio of 95:2.5:2.5 to prepare a positive electrode slurry (solid content of 70wt%), which was coated on the current collector aluminum foil and dried at 100°C to obtain a positive electrode sheet. The surface density of the positive electrode sheet was 80g / cm 2 The dried positive and negative electrode sheets are rolled, cut, wound, injected, sealed and formed to form a soft-pack full battery. 1.1 mol / L lithium bis(trifluoromethylsulfonyl)imide + EC:EMC:DEC (volume ratio 3:5:2) solution is used as the electrolyte, and the separator is Celgard2400.
[0113] The battery testing device was used to test the cycle performance. The battery capacity was calibrated at 25°C. The battery was then charged and discharged for 500 cycles at 3C charge / 0.5C discharge at 25°C, and the discharge capacity retention rate was calculated.
[0114] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments. The embodiments can be appropriately modified within the scope of the unchanged main rights.
[0115] Example 1
[0116] (1) Take 5 kg of artificial graphite primary particle material (D 50 =8μm, Tap=1.1g / cm 3 ,SSA=2.0m 2 / g) and 0.5Kg of solid asphalt were heated, mixed and granulated for 4 hours to obtain a composite.
[0117] (2) Take 5 kg of the complex, 0.3 kg of phenol, 5 kg of deionized water and 0.3 kg of ammonia water, and mechanically stir for 30 minutes to mix them evenly to obtain a mixed solution.
[0118] (3) 0.25 kg of formaldehyde solution was added to the mixed solution, and a polycondensation reaction was carried out under stirring for 3 hours. The obtained reaction product was separated into solid and liquid using a centrifuge to obtain a first precursor.
[0119] (4) The first precursor is placed in a vapor deposition reaction chamber, nitrogen-loaded titanium tetrachloride and nitrogen-loaded water vapor are introduced, and the mixture is heated to 260° C. for vapor deposition for 30 minutes to coat a layer of TiO 2 to obtain a second precursor.
[0120] (5) The second precursor is carbonized at a temperature of 1150° C. for 14 hours. The carbonized material is demagnetized and sieved to obtain a negative electrode material.
[0121] The negative electrode material prepared in the present application includes a core and a coating layer, wherein the core includes graphite, and the coating layer includes amorphous carbon and TiO2.
[0122] Figure 2 This is a scanning electron microscope image of the negative electrode material prepared in Example 1 of the present application. Figure 3 This is a transmission electron microscope image of the negative electrode material prepared in Example 1 of the present application, as shown Figure 2 and Figure 3 As shown, the negative electrode material particles are dispersed and the coating layer of the negative electrode material is relatively uniform.
[0123] Figure 4a Electron image of the negative electrode material prepared by 1 for this application. Figure 4b to Figure 4d The energy dispersive X-ray spectra (EDS) of different elements of the negative electrode material prepared by implementing 1 of the present application are shown in FIG. Figure 4a to Figure 4d As shown, C element, O element and Ti element exist on the surface of the negative electrode material.
[0124] Example 2
[0125] The difference from Example 1 is that
[0126] (1) Take 5 kg of artificial graphite secondary particle material (D 50 =13μm, Tap=1.0g / cm 3 ,SSA=2.0m 2 / g) and 0.5Kg of solid asphalt were heated, mixed and granulated for 4 hours to obtain a composite.
[0127] (2) Take 5 kg of the complex, 0.3 kg of cresol, 6 kg of deionized water and 0.3 kg of ammonia water, and mechanically stir for 30 minutes to mix them evenly to obtain a mixed solution.
[0128] Example 3
[0129] The difference from Example 1 is that
[0130] (1) Take 5 kg of artificial graphite secondary particle material (D 50 =13μm, Tap=1.0g / cm 3 ,SSA=2.0m 2 / g) and 0.8Kg of solid asphalt were heated, mixed and granulated for 5 hours to obtain a composite.
[0131] (2) 5 kg of the composite, 0.3 kg of resorcinol, 6 kg of deionized water and 0.3 kg of aqueous ammonia were taken and mechanically stirred for 30 min to mix uniformly to obtain a mixed solution.
[0132] The negative electrode material prepared in the present application includes a core and a coating layer, wherein the core includes graphite, and the coating layer includes amorphous carbon and TiO2.
[0133] Example 4
[0134] The difference from Example 1 is that
[0135] (1) Take 5 kg of composite material of primary and secondary particles of artificial graphite (D 50 =11.5μm, Tap=1.1g / cm 3 ,SSA=2.0m 2 / g, mass ratio is 3:7) and 0.5Kg of solid asphalt, and the mixture is heated, mixed and granulated for 4 hours to obtain a composite.
[0136] Example 5
[0137] The difference from Example 1 is that
[0138] (3) 0.5 kg of formaldehyde solution was added to the mixed solution, and a polycondensation reaction was carried out under stirring for 3 hours. The obtained reaction product was separated into solid and liquid using a centrifuge to obtain a first precursor.
[0139] Example 6
[0140] The difference from Example 1 is that
[0141] (3) 0.5 kg of furfural solution was added to the mixed solution, and a polycondensation reaction was carried out under stirring for 3 hours. The obtained reaction product was separated into solid and liquid using a centrifuge to obtain a first precursor.
[0142] Example 7
[0143] The difference from Example 6 is that
[0144] (1) Take 5 kg of composite material of primary and secondary particles of artificial graphite (D 50 =9.5μm, Tap=1.05g / cm 3 ,SSA=2.0m 2 / g, mass ratio is 7:3) and 0.5Kg of solid asphalt, and the mixture is heated, mixed and granulated for 4 hours to obtain a composite.
[0145] Example 8
[0146] (1) Take 5 kg of artificial graphite primary particle material (D 50 =6.5μm, Tap=0.89g / cm 3 , SSA=4.2m 2 / g) and 0.5Kg of solid asphalt were heated, mixed and granulated for 4 hours to obtain a composite.
[0147] (2) Take 5 kg of the complex, 0.3 kg of phenol, 5 kg of deionized water and 0.3 kg of ammonia water, and mechanically stir for 30 minutes to mix them evenly to obtain a mixed solution.
[0148] (3) 0.25 kg of formaldehyde solution was added to the mixed solution, and a polycondensation reaction was carried out under stirring for 3 hours. The obtained reaction product was separated into solid and liquid using a centrifuge to obtain a first precursor.
[0149] (4) The first precursor is placed in a vapor deposition reaction chamber, nitrogen-loaded niobium pentachloride and nitrogen-loaded water vapor are introduced, and the mixture is heated to 300° C. for vapor deposition for 30 minutes to coat a layer of Nb2O5, thereby obtaining a second precursor.
[0150] (5) The second precursor is carbonized at a temperature of 1150° C. for 14 hours. The carbonized material is demagnetized and sieved to obtain a negative electrode material.
[0151] The negative electrode material prepared in the present application includes a core and a coating layer, wherein the core includes graphite, and the coating layer includes amorphous carbon and Nb2O5.
[0152] Example 9
[0153] The difference from Example 8 is that
[0154] (2) 5 kg of the complex, 0.3 kg of nonylphenol, 5 kg of deionized water and 0.3 kg of aqueous ammonia were taken and mechanically stirred for 9 hours to mix them evenly to obtain a mixed solution.
[0155] Example 10
[0156] The difference from Example 8 is that
[0157] (2) Take 5 kg of the complex, 0.3 kg of aralkylphenol, 5 kg of deionized water and 0.3 kg of ammonia water, and mechanically stir for 12 hours to mix them evenly to obtain a mixed solution.
[0158] Embodiment 11
[0159] The difference from Example 4 is that
[0160] (2) Take 5 kg of the complex, 0.3 kg of phenol, 5 kg of deionized water and 0.3 kg of sodium hydroxide, and mechanically stir for 30 minutes to mix them evenly to obtain a mixed solution.
[0161] Example 12
[0162] The difference from Example 4 is that
[0163] (2) Take 5 kg of the complex, 0.3 kg of phenol, 5 kg of deionized water and 0.3 kg of oxalic acid, and mechanically stir for 30 minutes to mix them evenly to obtain a mixed solution.
[0164] Example 13
[0165] The difference from Example 1 is that
[0166] (5) The second precursor is carbonized at a temperature of 800° C. for 14 hours. The carbonized material is demagnetized and sieved to obtain a negative electrode material.
[0167] Embodiment 14
[0168] The difference from Example 1 is that
[0169] (5) The second precursor is carbonized at a carbonization temperature of 1400° C. for 14 hours. The carbonized material is demagnetized and sieved to obtain a negative electrode material.
[0170] Embodiment 15
[0171] The difference from Example 1 is that
[0172] (5) The second precursor is carbonized at a temperature of 1150° C. for 3 hours. The carbonized material is demagnetized and sieved to obtain a negative electrode material.
[0173] Example 16
[0174] The difference from Example 1 is that
[0175] (2) Take 5 kg of the complex, 0.1 kg of phenol, 5 kg of deionized water and 0.3 kg of aqueous ammonia, and mechanically stir for 30 minutes to mix them evenly to obtain a mixed solution.
[0176] (3) 0.11 kg of formaldehyde solution was added to the mixed solution, and a polycondensation reaction was carried out under stirring for 3 hours. The obtained reaction product was separated into solid and liquid using a centrifuge to obtain a first precursor.
[0177] Comparative Example 1
[0178] The difference from Example 1 is that no catalyst ammonia water is added.
[0179] Comparative Example 2
[0180] The difference from Example 1 is that
[0181] (5) The second precursor is carbonized at a temperature of 200° C. for 14 hours. The carbonized material is demagnetized and sieved to obtain a negative electrode material.
[0182] Comparative Example 3
[0183] The difference from Example 1 is that
[0184] (3) 0.07 kg of formaldehyde solution was added to the mixed solution, and a polycondensation reaction was carried out under stirring for 3 hours. The obtained reaction product was separated into solid and liquid using a centrifuge to obtain a first precursor.
[0185] Comparative Example 4
[0186] The difference from Example 1 is that
[0187] (3) 0.25 kg of formaldehyde solution was added to the mixed solution, and a polycondensation reaction was carried out under stirring for 2 hours. The obtained reaction product was separated into solid and liquid using a centrifuge to obtain a first precursor.
[0188] Comparative Example 5
[0189] The difference from Example 1 is that
[0190] (2) Take 5 kg of the complex, 0.80 kg of phenol, 5 kg of deionized water and 0.3 kg of ammonia water, and mechanically stir for 30 minutes to mix them evenly to obtain a mixed solution.
[0191] (3) 1.2 kg of formaldehyde solution was added to the mixed solution, and a polycondensation reaction was carried out under stirring for 3 hours. The obtained reaction product was separated into solid and liquid using a centrifuge to obtain a first precursor.
[0192] The negative electrode materials obtained in the examples and comparative examples were subjected to performance tests. The results of the performance tests are shown in Tables 1 and 2:
[0193] Table 1. Performance test results of various embodiments and comparative examples
[0194]
[0195]
[0196] Table 2 Summary of the electrochemical performance test results of negative electrode materials
[0197]
[0198] According to the data in Table 1 and Table 2, for the negative electrode materials of Examples 1 to 16, when the average value of the peak area ratio of the first characteristic peak to the second characteristic peak of the negative electrode material is A in the range of 2 to 3, the degree of surface defects of the negative electrode material particles is controlled within an appropriate range, and an appropriate amount of surface defects can provide more electrochemically active sites, which is beneficial to improving the capacity of the negative electrode material; and the fast ion conductors in the coating layer are used to increase the ion transmission channels and improve the lithium ion transmission rate of the negative electrode material; the distribution width of the peak area ratio data is synergistically controlled to be within the range of 0.5, the surface disorder degree of each particle is closer, the ion transmission efficiency between different particles can be improved, and the negative electrode material can meet the fast charging performance.
[0199] According to Example 16, compared with Example 1, due to the small amount of phenolic reagents and aldehyde reagents added, the content of the polymer coated on the surface of the graphite particles is reduced, and the surface disorder of the negative electrode material finally obtained is also reduced. The average value of the peak area ratio of the first characteristic peak of the negative electrode material to the second characteristic peak is A, and the P value is increased compared with Example 1. (AB) / P also decreases accordingly, and the coverage integrity and uniformity of the coating layer on the surface of the negative electrode material decrease. The fast charging performance and first efficiency of the negative electrode material are slightly reduced compared with Example 1. Preferably, (AB) / P>3.
[0200] According to Comparative Example 1 compared with Example 1, Comparative Example 1 does not add a catalyst, resulting in lower reaction activity of phenolic reagents and aldehyde reagents, reduced integrity and uniformity of the surface coating of the graphite particles, and partial exposure of the graphite on the surface, resulting in a significant decrease in the average value A of the peak area ratio of the first characteristic peak of the negative electrode material to the second characteristic peak, an increase in the distribution width P of the peak area ratio data, a decrease in the uniformity of the coating layer on the surface of the negative electrode material, and a decrease in the particle strength. The difference in the degree of surface disorder of the negative electrode material particles increases, which increases the difference in the rate of lithium ion insertion and extraction between the particles, resulting in poor fast charging performance of the negative electrode material.
[0201] According to Comparative Example 2 compared with Example 1, the carbonization temperature of Comparative Example 2 is 200°C. At this temperature, it is difficult for the polymer molecular chain to be fully converted into amorphous carbon with a dense structure, and there are many oxygen-containing functional groups and defects, resulting in a decrease in the average value A of the peak area ratio of the first characteristic peak of the negative electrode material to the second characteristic peak, an increase in the distribution width P of the peak area ratio data, a decrease in the uniformity of the coating layer on the surface of the negative electrode material, an intensification of the side reaction between the negative electrode material and the electrolyte, a decrease in the first coulombic efficiency of the negative electrode material, a decrease in the capacity, and a poor fast charging performance.
[0202] According to Comparative Example 3 compared with Example 1, the formaldehyde addition amount of Comparative Example 3 is too low, the condensation reaction is not sufficient, the generated polymer molecular chains are relatively small, the surface coating integrity and uniformity of the graphite particles are reduced, part of the graphite is exposed on the surface, and the average value A of the peak area ratio of the first characteristic peak to the second characteristic peak of the negative electrode material of Comparative Example 3 is reduced, the distribution width P of the peak area ratio data is increased, the uniformity of the coating layer on the surface of the negative electrode material is reduced, and the difference in the rate of lithium ion insertion and extraction between the negative electrode material particles is increased, resulting in poor fast charging performance of the negative electrode material.
[0203] According to Comparative Example 4 compared with Example 1, the condensation reaction time of Comparative Example 4 is too short, and the surface coating integrity and uniformity of the graphite particles are reduced, resulting in a significant decrease in the average value A of the peak area ratio of the first characteristic peak of the negative electrode material to the second characteristic peak. Although the data distribution width P still meets the requirements, the fast charging performance of the negative electrode material is still significantly reduced compared to Example 1.
[0204] According to Comparative Example 5 compared with Example 1, excessive addition of phenol and formaldehyde makes the coating layer too thick, the side reactions increase, and the capacity and the first coulombic efficiency of the negative electrode material decrease. Although the average value A of the peak area ratio of the negative electrode material can meet the demand, the excessively thick coating layer makes the distribution width P of the peak area ratio data between different particles too large, and the difference in the degree of surface disorder of each particle increases, which increases the difference in the rate of lithium ion insertion and extraction between the particles, resulting in poor fast charging performance of the negative electrode material.
[0205] Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the claims. Any technical personnel in this field may make several possible changes and modifications without departing from the concept of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined by the claims of the present application.
Claims
1. A negative electrode material, characterized in that: The negative electrode material comprises a core and a coating layer, wherein the core comprises graphite, and the coating layer comprises amorphous carbon and a fast ion conductor; The negative electrode material is tested by Raman scanning to obtain i Raman spectrum curves, i>2000; each Raman spectrum curve has a peak at 1345 cm -1 ~1355cm -1 There is a first characteristic peak in the wavelength range, at 1570cm -1 ~1610cm -1 There is a second characteristic peak within the wavelength range; in the i Raman spectra, the average value of the peak area ratio of the first characteristic peak to the second characteristic peak is A, 2.0≤A≤3.0; the distribution width of the peak area ratio data of the i Raman spectra is P, P<0.
5.
2. The negative electrode material according to claim 1, characterized in that In the i Raman spectra, the average value of the peak intensity ratio of the first characteristic peak to the second characteristic peak is B, and 0.7≤B≤1.
5.
3. The negative electrode material according to claim 2, characterized in that (AB) / P>3.
4. The negative electrode material according to claim 1, characterized in that The negative electrode material includes at least one of the following features: (1) The average particle strength of the negative electrode material is Q%, Q / A<5.0; (2) The average particle strength of the negative electrode material is Q%, 1≤Q≤15.
5. The negative electrode material according to any one of claims 1 to 4, characterized in that: The graphite includes at least one of natural graphite and artificial graphite.
6. The negative electrode material according to any one of claims 1 to 4, characterized in that The fast ion conductor includes at least one of a titanium ion compound, a niobium ion compound and a vanadium ion compound; and / or, the fast ion conductor is distributed in the amorphous carbon.
7. The negative electrode material according to any one of claims 1 to 4, characterized in that The average thickness of the coating layer is 5nm to 20nm.
8. The negative electrode material according to any one of claims 1 to 4, characterized in that The negative electrode material includes at least one of the following features: (1) The volume median particle size D50 of the negative electrode material is 2 μm to 20 μm; (2) The specific surface area of the negative electrode material is 0.5 m 2 / g~5m 2 / g; (3) The tap density of the negative electrode material is 0.5 g / cm 3 ~1.5g / cm 3 .
9. The negative electrode material according to any one of claims 1 to 4, characterized in that: The lithium ion diffusion coefficient of the negative electrode material is greater than or equal to 0.49*10 -7 cm 2 / S.
10. A battery, characterized in that: The negative electrode material comprises the negative electrode material as claimed in any one of claims 1 to 9.